Identifying nature-positive futures in new cities: an application of the Urban Nature Futures Framework - Shaikh Fairul Edros bin Shaikh Ahmad (2024)
With the increasing loss of biodiversity due to urbanization, it is essential to examine and re-imagine the place of nature in cities. The opportunity to redesign positive relationships between cities and nature is particularly apparent in the development of new cities—rapidly developing areas observed in many Asian and African countries. As these new cities are built on a perceived tabula rasa, there is a potential to design positive nature futures. This study, therefore, aims to understand how nature is incorporated into existing plans for new cities and identify pro-nature perspectives envisioned within these plans. We use the Urban Nature Futures Framework (UNFF) to conduct a content analysis on the masterplans of new city and town developments within the Jakarta Metropolitan Area (JMA). The UNFF promotes the creation of multiple positive visions of nature in cities by considering three broad nature perspectives: Nature for Nature, Nature for Society, and Nature as Culture, as well as emphasizing equity in these visions. Our findings show that the Nature for Society perspective tends to dominate the design of new cities in the JMA, closely followed by the Nature for Nature perspective embodied by pollution control measures. New cities also emphasise the Nature as Culture perspective through nature stewardship programmes. Based on these results, we exemplify how the UNFF can be used to further integrate nature elements in new cities’ masterplans. We conclude with a discussion of the strengths and limitations of the framework at each stage of the new city development process.